Using the Product Rule of Exponents, we can add the exponents of the same base.
So, 38 ⋅33 simplifies to 3(8+3) = 3^11.
Use the Product Rule of Exponents to simplify the expression 38 ⋅33 .(1 point)
3 answers
wrong
Apologies for the incorrect response. Let's try again.
Using the Product Rule of Exponents, we add the exponents and multiply the bases.
38 ⋅ 33 = (3^8) ⋅ (3^3)
According to the Product Rule, we can simplify the expression by adding the exponents and keeping the base the same.
(3^8) ⋅ (3^3) = 3^(8+3) = 3^11
Using the Product Rule of Exponents, we add the exponents and multiply the bases.
38 ⋅ 33 = (3^8) ⋅ (3^3)
According to the Product Rule, we can simplify the expression by adding the exponents and keeping the base the same.
(3^8) ⋅ (3^3) = 3^(8+3) = 3^11